2018
DOI: 10.1183/13993003.01150-2018
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive sleep apnoea as a risk factor for incident metabolic syndrome: a joined Episono and HypnoLaus prospective cohorts study

Abstract: @ERSpublications REM sleep-disordered breathing is highly prevalent and is associated with metabolic syndrome and diabetes ABSTRACT This study determined the prevalence of rapid eye movement (REM) related sleepdisordered breathing (REM-SDB) in the general population and investigated the associations of REM-SDB with hypertension, metabolic syndrome, diabetes and depression.Home polysomnography (PSG) recordings (n=2074) from the population-based HypnoLaus Sleep Cohort (48.3% men, 57±11 years old) were analysed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 72 publications
0
40
0
6
Order By: Relevance
“…It is estimated that a large proportions of individuals with OSA are undiagnosed and untreated [3], [4], [5]. Several studies have shown that if untreated, OSA increases the risk of cardiovascular diseases [6], metabolic syndrome [7] and diabetes [8]. Undiagnosed and untreated OSA is associated with behavioral alteration [9], workplace productivity losses and increased motor vehicle accidents due to sleepiness on the road, leading to high clinical and economical costs [10].…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that a large proportions of individuals with OSA are undiagnosed and untreated [3], [4], [5]. Several studies have shown that if untreated, OSA increases the risk of cardiovascular diseases [6], metabolic syndrome [7] and diabetes [8]. Undiagnosed and untreated OSA is associated with behavioral alteration [9], workplace productivity losses and increased motor vehicle accidents due to sleepiness on the road, leading to high clinical and economical costs [10].…”
Section: Introductionmentioning
confidence: 99%
“…Abdominal visceral fat and intramuscular ectopic fat deposits are pro-inflammatory, diabetogenic and atherogenic (A) 18 . Intramuscular fat deposits in the tongue cause the tongue to enlarge, encroach on the upper airway lumen and increase the risk of OSA (B) 22,23 attributed to OSA to be overestimated including in studies of incident diabetes 28 , hypertension 9 and metabolic syndrome 29 . Visceral fat is the main source of circulating biomarkers of inflammation.…”
Section: Cohort Studiesmentioning
confidence: 99%
“…A recent cohort study evaluated the influence of OSAS on the incidence of metabolic syndrome in a multiethnic sample of 1853 people from two population-based samples (Episono in Brazil and HypnoLaus in Switzerland) [63]. Participants included in the analysis were mainly female (56%) and Caucasian (88%), with an average age of 51.9 (±13.1) years and a BMI of 24.9 (±3.7) kg/m 2 .…”
Section: Obstructive Sleep Apnea and Metabolic Syndromementioning
confidence: 99%